Sodium ion battery and application thereof
By introducing gas-producing particles and catalysts into the positive electrode active material layer of the sodium ion battery, and combining the adjustment of the CID trigger threshold, the safety risks of sodium ion battery under overcharge and thermal abuse are solved, and the battery cell temperature control and the risk of combustion and explosion are reduced.
Patent Information
- Application Number
- CN202510907210.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2025-08-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Sodium ion batteries have safety risks in overcharge and thermal abuse conditions, including untimely triggering of current interruption devices (CIDs), high risk of thermal runaway due to low gas production rates, and high flammability of gas-producing components exacerbating the risk of ignition and explosion.
In the positive electrode active material layer, sodium carbonate and/or sodium oxalate are introduced as gas-producing particles, iron chloride and/or aluminum chloride are used as catalysts, and the trigger threshold of the current interruption device (CID) is adjusted to 0.55MPa-0.85MPa. The gas-producing reaction is triggered when the internal temperature of the battery rises through catalytic action, and the CID is driven to disconnect the current circuit or open the pressure relief channel to achieve safety protection.
Effectively control the battery cell temperature below the critical point of thermal runaway, eliminate the risk of thermal runaway, and reduce the risk of combustion and explosion by generating CO2 and CO, and improve battery safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly to sodium-ion batteries and their applications. Background Art
[0002] Due to advantages such as rich sodium resources and low cost, sodium-ion batteries are gradually being applied to energy storage and electric transportation. However, their safety still faces severe challenges. For example: (1) During overcharging, the rate of gas generation by the decomposition of the electrolyte is low, resulting in a trigger voltage of the current interruption device (CID) as high as 4.3V - 4.4V. At this time, sodium dendrites have grown on a large scale, easily piercing the separator and causing a short circuit, further releasing a large amount of heat, and ultimately leading to thermal runaway; (2) Under thermal abuse conditions, the CID relies on the gasification and pressurization of the electrolyte to trigger. However, the rate of gas generation by the decomposition of the electrolyte is low, resulting in the inability to effectively cut off the circuit in the early stage of thermal runaway, and ultimately leading to thermal runaway; (3) The traditional gas generation is mainly H2 / CH4, with a volume ratio exceeding 50%, and high flammability, which will increase the risk of combustion and explosion after thermal runaway. Summary of the Invention
[0003] Based on this, in view of the above problems, it is necessary to provide a sodium-ion battery and its application. The sodium-ion battery can solve the safety hazards of traditional sodium-ion batteries under overcharging and thermal abuse conditions by optimizing the synergistic effect of the gas generation mechanism inside the battery cell and the CID trigger threshold.
[0004] A sodium-ion battery includes a positive electrode sheet, a separator, a negative electrode sheet, an electrolyte, and a current interruption device. The sodium-ion battery satisfies the following two conditions:
[0005] (1) The positive electrode active material layer of the positive electrode sheet contains gas generation particles and a catalyst. Among them, the gas generation particles are selected from sodium carbonate and / or sodium oxalate, and the catalyst is selected from ferric chloride and / or aluminum chloride. The mass fraction of the gas generation particles in the positive electrode active material layer is greater than the mass fraction of the catalyst in the positive electrode active material layer, and the sum of the mass fractions of the gas generation particles and the catalyst in the positive electrode active material layer is within 4%;
[0006] (2) The trigger threshold of the current interruption device is 0.55MPa - 0.85MPa.
[0007] In one embodiment, the mass ratio of the gas generation particles to the catalyst is 5:1 - 10:1.
[0008] In one embodiment, the mass fraction of the gas generation particles in the positive electrode active material layer is above 0.5%, and the mass fraction of the catalyst in the positive electrode active material layer is below 0.8%.
[0009] In one embodiment, the mass fraction of the gas-generating particles in the positive electrode active material layer is 0.5% - 3%.
[0010] In one embodiment, the mass fraction of the catalyst in the positive electrode active material layer is 0.1% - 0.6%.
[0011] In one embodiment, the particle size of the gas-generating particles is 0.1 μm - 10 μm.
[0012] In one embodiment, the positive electrode active material layer at least includes a layered metal oxide positive electrode material.
[0013] In one embodiment, the trigger threshold of the current interruption device is 0.65 MPa - 0.75 MPa.
[0014] In one embodiment, the response time of the current interruption device is less than 10 seconds.
[0015] An application of the sodium ion battery as described above in a battery module or a battery pack.
[0016] In the present invention, sodium carbonate and / or sodium oxalate are introduced as gas-generating particles, and ferric chloride and / or aluminum chloride are introduced as catalysts in the positive electrode active material layer. At the same time, the trigger threshold of the CID is adjusted to 0.55 MPa - 0.85 MPa. When the internal temperature of the battery rises above 70 °C, under the catalytic action of the catalyst, the gas-generating particles trigger a primary gas-generation reaction, and the generated gas rapidly increases the internal pressure, driving the solder joint of the CID to break, forming a permanent open circuit, thereby cutting off the current loop and achieving primary safety protection. If the reaction is violent or the primary safety protection is not completely effective and the abnormal situation persists, resulting in the temperature further rising above 130 °C, the gas-generating particles will further trigger a secondary gas-generation reaction. At this stage, the gas pressure generated is higher, which will push the CID to reverse and open the pressure relief channel for rapid gas release to provide additional deep protection.
[0017] Therefore, by optimizing the synergistic effect of the internal gas-generation mechanism of the battery cell and the trigger threshold of the CID, the sodium ion battery of the present invention ensures that the internal temperature of the battery cell is always controlled below the thermal runaway critical point of 150 °C during overcharging or thermal abuse conditions, thereby eliminating the risk of thermal runaway. In addition, the CO2 gas generated by the reaction of the gas-generating particles in the present invention and a small amount of CO reduced from CO2 will form a mixed gas with H2 / CH4, and the volume ratio of CO / CO2 can reach more than 40%, thereby reducing the risk of combustion and explosion. Detailed implementation manners
[0018] For the convenience of understanding the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, these embodiments or examples are provided to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present invention belongs. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments or examples and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of the related listed items. The any and all combinations include any two related listed items, any more related listed items, or the combination of all related listed items.
[0020] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when the range refers to integers, it includes each integer between the minimum and maximum values of the range. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges subsumed therein.
[0021] In order to improve the safety of sodium-ion batteries, additives can be introduced to increase the gas production. However, the proportion of the additives and the possible side reactions will both lead to the attenuation of the electrochemical performance of sodium-ion batteries; or, the triggering threshold of the CID can be lowered so that it can respond in advance. However, if the triggering threshold of the CID is too low, it is easy to cause false triggering due to the natural gasification of the electrolyte, reducing the reliability of the battery.
[0022] Therefore, the sodium-ion battery provided by the present invention includes a positive electrode sheet, a separator, a negative electrode sheet, an electrolyte, and a current interruption device, and the sodium-ion battery satisfies the following two conditions:
[0023] (1) The positive electrode active material layer of the positive electrode sheet contains gas-producing particles and a catalyst. Among them, the gas-producing particles are selected from sodium carbonate and / or sodium oxalate, and the catalyst is selected from iron chloride and / or aluminum chloride. The mass fraction of the gas-producing particles in the positive electrode active material layer is greater than the mass fraction of the catalyst in the positive electrode active material layer, and the sum of the mass fractions of the gas-producing particles and the catalyst in the positive electrode active material layer is within 4%.
[0024] (2)The triggering threshold of the current interruption device is 0.55 MPa - 0.85 MPa.
[0025] In the present invention, sodium carbonate and / or sodium oxalate are introduced as gas-producing particles, and ferric chloride and / or aluminum chloride are used as catalysts in the positive electrode active material layer, and the sum of the mass fractions of the gas-producing particles and the catalysts in the positive electrode active material layer is controlled within 4%, thereby basically not affecting the electrochemical performance of the sodium-ion battery.
[0026] Meanwhile, after the triggering threshold of the CID is adjusted to 0.55 MPa - 0.85 MPa, when the internal temperature of the battery rises above 70 °C due to factors such as overcharging or thermal abuse, under the catalytic action of the catalyst, the gas-producing particles trigger the primary gas generation reaction, and the generated gas rapidly increases the internal pressure, driving the solder joint of the CID to disconnect, forming a permanent open circuit, thereby cutting off the current loop and realizing the primary safety protection. At this time, if the reaction is violent or the primary safety protection is not completely effective and the abnormal situation continues, resulting in the temperature further rising above 130 °C, the gas-producing particles will further trigger the secondary gas generation reaction. The gas pressure generated in this stage is higher, which will push the CID to reverse and open the pressure relief channel for rapid deflation to provide additional deep protection.
[0027] Specifically, the thermal decomposition temperatures of sodium carbonate and sodium oxalate are both above 200 °C, which can ensure that they will not decompose during the preparation of the positive electrode sheet, but will also cause problems with the gas generation efficiency during use. The catalysts ferric chloride and aluminum chloride can form intermediate complexes with sodium carbonate and sodium oxalate, such as 2- 、[Al(CO3)Cl3] 2- 、[Fe(CO3)Cl3] 2- or [Fe(C2O4)Cl3] 2- etc., and then can reduce the thermal decomposition temperature and achieve the effect of rapid gas generation.
[0028] Further, taking ferric chloride catalyst as an example, the reaction formulas for the primary gas generation reaction of sodium carbonate and sodium oxalate triggered by the catalyst are as follows:
[0029] 2Na2CO3 + 2FeCl3 → 2FeOCl + 4NaCl + 2CO2↑
[0030] Na2C2O4 + 2FeCl3 → 2NaCl + 2FeCl2 + 2CO2↑
[0031] The reaction formulas for the secondary gas generation reaction of sodium carbonate and sodium oxalate triggered by the catalytic action are as follows:
[0032] Na2C2O4 + 1 / 2O2 → Na2CO3 + CO2↑
[0033] 2Na2CO3→2Na2O+2CO2↑
[0034] Therefore, through the synergistic effect of optimizing the gas generation mechanism inside the battery cell and the CID trigger threshold, the sodium-ion battery of the present invention can ensure that the internal temperature of the battery cell is always controlled below the thermal runaway critical point of 150°C during overcharging or thermal abuse conditions, thereby eliminating the risk of thermal runaway.
[0035] In addition, from the reaction formulas of the above primary gas generation reaction and secondary gas generation reaction, it can be seen that the gas generation particles of the present invention will react to generate a large amount of CO2 gas during the primary gas generation reaction and secondary gas generation reaction stages. The generated CO2 gas will also be slightly reduced to produce CO gas, and will form a mixed gas with H2 / CH4, and the volume ratio of CO / CO2 can reach more than 40%, thereby reducing the risk of combustion and explosion.
[0036] In order to further optimize the gas generation amount and gas generation efficiency, the sum of the mass fractions of the gas generation particles and the catalyst in the positive electrode active material layer is preferably controlled between 0.6% and 4%. Among them, the mass fraction of the gas generation particles in the positive electrode active material layer is above 0.5%, and the mass fraction of the catalyst in the positive electrode active material layer is below 0.8%. At the same time, the mass ratio of the gas generation particles to the catalyst is preferably 5:1 - 10:1. More specifically, the mass fraction of the gas generation particles in the positive electrode active material layer is preferably 0.5% - 3%, and the mass fraction of the catalyst in the positive electrode active material layer is preferably 0.1% - 0.6%.
[0037] In addition, the smaller the particle size of the gas generation particles, the more beneficial it is to improve the gas generation efficiency. However, considering that the gas generation particles with smaller particle sizes are more likely to agglomerate, preferably, the particle size of the gas generation particles is 0.1μm - 10μm.
[0038] It can be understood that in the positive electrode sheet, the positive electrode active material layer also includes positive electrode active material, conductive agent, binder, etc. In the sodium-ion battery of the present invention, it is preferred that the positive electrode active material layer at least includes a layered metal oxide positive electrode material. For example, the positive electrode active material of the positive electrode active material layer is a layered metal oxide positive electrode material, or the positive electrode active material is a composite material or a mixed material of a layered metal oxide positive electrode material and a polyanion-based positive electrode material, etc.
[0039] In the present invention, there are no special requirements for the selection and mass ratio of positive electrode active materials such as layered metal oxide positive electrode materials and polyanion-based positive electrode materials, conductive agents, and binders, and they can be selected and controlled according to the conventional method. For example, the chemical formula of the layered metal oxide positive electrode material is Na xMO₂, where M is selected from at least one of Fe, Co, Ni, and Mn, and 0 < x ≤ 1; the conductive agent is selected from carbon nanotubes (CNT), conductive carbon black (SP), acetylene black, Ketjen black, conductive graphite, etc., and the binder is selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), sodium alginate, styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), etc. Details are not elaborated herein in the present invention.
[0040] In order to make the gas generation mechanism inside the battery cell match better with the CID trigger threshold and have a better coordination effect, the trigger threshold of the current interruption device in the present invention is further preferably 0.65 MPa - 0.75 MPa.
[0041] Furthermore, the response time of the current interruption device can be optimized to be less than 10 seconds, making the response speed of CID faster.
[0042] It should be noted that the present invention has no special requirements for the negative electrode, separator, and electrolyte of the sodium-ion battery, and conventional designs can be selected. For example, the active material of the negative electrode is selected from hard carbon materials, soft carbon materials, graphite, etc., the conductive agent is selected from carbon nanotubes (CNT), conductive carbon black (SP), acetylene black, Ketjen black, conductive graphite, etc., and the binder is selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), sodium alginate, styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), etc.; the separator is selected from polypropylene separator (PP), polyimide separator (PI), polyethylene separator (PE), PE ceramic membrane (with a ceramic coating on the polyethylene membrane), and PE ceramic membrane is preferred; the electrolyte contains sodium salts and organic solvents, where the sodium salts are selected from NaPF₆, etc., and the organic solvents are selected from ethylene carbonate (EC), dimethyl carbonate (DMC), etc. Details are not elaborated herein in the present invention.
[0043] The present invention has no requirements for the form of the sodium-ion battery, which can be a cylindrical battery, a square battery, etc.
[0044] Therefore, by optimizing the synergistic effect between the gas generation mechanism inside the battery cell and the CID trigger threshold, the sodium-ion battery of the present invention can solve the safety hazards of traditional sodium-ion batteries under overcharge and thermal abuse conditions.
[0045] The present invention also provides an application of the sodium-ion battery described above in a battery module or a battery pack. Thus, the battery module or battery pack applying the sodium-ion battery of the present invention has more reliable safety.
[0046] The technical solution of the present invention will be further described below through the following specific embodiments. However, those skilled in the art will understand that the following embodiments are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. For those conditions not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. For the reagents or instruments whose manufacturers are not specified, they are all conventional products that can be obtained through commercial purchase.
[0047] Example 1
[0048] Weigh NaNi 0.6 Mn 0.3 Fe 0.1 O2, Na2CO3 particles with a particle size of 5 μm, FeCl3, acetylene black, and PVDF according to the mass ratio of 94.4:0.5:0.1:3.5:1.5. Then, first premix the Na2CO3 particles and FeCl3 to form a mixture, and then disperse the mixture, NaNi 0.6 Mn 0.3 Fe 0.1 O2, acetylene black, and PVDF in NMP solvent to form a positive electrode paste. Then, uniformly coat the positive electrode paste on an aluminum foil current collector, and after vacuum drying at 120 °C, punch it into a positive electrode sheet.
[0049] Disperse soft carbon negative electrode particles, acetylene black, and CMC in NMP solvent according to the mass ratio of 95:3.5:1.5 to form a negative electrode paste. Then, uniformly coat the negative electrode paste on a copper foil current collector, and after vacuum drying at 60 °C, punch it into a negative electrode sheet.
[0050] Use NaPF6 as the sodium salt, dissolve NaPF6 in a mixed solvent of EC / DMC with a volume ratio of 4:6, and then add 1 wt% of fluoroethylene carbonate (FEC) as a film-forming additive to obtain an electrolyte. Among them, the concentration of the sodium salt in the electrolyte is 1.0 mol / L, and the conductivity of the electrolyte is ~12 mS / cm (25 °C).
[0051] Use a PE ceramic membrane (a PE separator loaded with 10 wt% BN), with a thickness of 13 μm.
[0052] Use a mechanically deformed trigger type CID, set the trigger threshold to 0.7 ± 0.05 MPa, and verify that the response time < 10 seconds through the spring stiffness coefficient.
[0053] Then stack the above positive electrode sheet, negative electrode sheet, and separator into a 32700 cylindrical battery cell, then inject the electrolyte, and the injection amount of the electrolyte is 3.5 g / Ah. After that, install the CID device and the cap, and after vacuum packaging, pre-charge (0.1C), age (48 h), and form (0.2C) to activate, and obtain a sodium-ion battery.
[0054] Example 2
[0055] Weigh NaNi 0.6 Mn 0.3 Fe 0.1 O2, Na2C2O4 particles with a particle size of 1 μm, AlCl3, acetylene black, and PVDF according to a mass ratio of 91.5:3:0.5:3.5:1.5. Then, first premix the Na2C2O4 particles and AlCl3 to form a mixture, and then disperse the mixture, NaNi 0.6 Mn 0.3 Fe 0.1 O2, acetylene black, and PVDF in NMP solvent to form a positive electrode slurry. Then, uniformly coat the positive electrode slurry on an aluminum foil current collector, and after vacuum drying at 120 °C, punch it into a positive electrode sheet.
[0056] Disperse soft carbon negative electrode particles, acetylene black, and CMC in NMP solvent according to a mass ratio of 95:3.5:1.5 to form a negative electrode slurry. Then, uniformly coat the negative electrode slurry on a copper foil current collector, and after vacuum drying at 60 °C, punch it into a negative electrode sheet.
[0057] Use NaPF6 as the sodium salt, dissolve NaPF6 in a mixed solvent of EC / DMC with a volume ratio of 4:6, and then add 1 wt% of fluoroethylene carbonate (FEC) as a film-forming additive to obtain an electrolyte. Among them, the concentration of the sodium salt in the electrolyte is 1.0 mol / L, and the conductivity of the electrolyte is ~12 mS / cm (25 °C).
[0058] Use a PE ceramic membrane (a PE separator loaded with 10 wt% BN), with a thickness of 13 μm.
[0059] Adopt a mechanically deformed trigger type CID, set the trigger threshold to 0.7 ± 0.05 MPa, and verify that the response time < 10 seconds through the spring stiffness coefficient.
[0060] Then stack the above positive electrode sheet, negative electrode sheet, and separator into a 32700 cylindrical battery cell, then inject the electrolyte, the injection amount of the electrolyte is 3.5 g / Ah, and then install the CID device and the cap. After vacuum packaging, it is pre-charged (0.1C), aged (48 h), and formed (0.2C) to activate, obtaining a sodium-ion battery.
[0061] Example 3
[0062] Weigh NaNi 0.6 Mn 0.3 Fe 0.1 O2, Na2CO3 particles with a particle size of 1 μm, FeCl3, acetylene black, and PVDF according to a mass ratio of 93.8:1:0.2:3.5:1.5. Then, first premix the Na2CO3 particles and FeCl3 to form a mixture, and then disperse the mixture, NaNi0.6 Mn 0.3 Fe 0.1 O2, acetylene black, and PVDF are dispersed in NMP solvent to form a positive electrode paste. Then, the positive electrode paste is uniformly coated on an aluminum foil current collector and punched into positive electrode sheets after vacuum drying at 120 °C.
[0063] Soft carbon negative electrode particles, acetylene black, and CMC are dispersed in NMP solvent in a mass ratio of 95:3.5:1.5 to form a negative electrode paste. Then, the negative electrode paste is uniformly coated on a copper foil current collector and punched into negative electrode sheets after vacuum drying at 60 °C.
[0064] NaPF6 is used as the sodium salt. NaPF6 is dissolved in a mixed solvent of EC / DMC with a volume ratio of 4:6, and then 1 wt% of fluoroethylene carbonate (FEC) is added as a film-forming additive to obtain an electrolyte. Among them, the concentration of the sodium salt in the electrolyte is 1.0 mol / L, and the conductivity of the electrolyte is ~12 mS / cm (25 °C).
[0065] A PE ceramic membrane (a PE separator loaded with 10 wt% BN) with a thickness of 13 μm is used.
[0066] A mechanically deformed triggered CID is adopted, the trigger threshold is set to 0.6 ± 0.05 MPa, and the response time is verified to be <10 s through the spring stiffness coefficient.
[0067] Then, the above positive electrode sheets, negative electrode sheets, and separator are stacked into a 32700 cylindrical battery cell, and then the electrolyte is injected. The injection amount of the electrolyte is 3.5 g / Ah. After that, the CID device and the cap are installed, and after vacuum packaging, it is pre-charged (0.1C), aged (48 h), and formed (0.2C) to be activated to obtain a sodium-ion battery.
[0068] Example 4
[0069] Weigh NaNi, 0.6 Mn 0.3 Fe 0.1 O2, Na2CO3 particles with a particle size of 1 μm, FeCl3, acetylene black, and PVDF in a mass ratio of 92.7:2:0.3:3.5:1.5. First, the Na2CO3 particles and FeCl3 are premixed to form a mixture, and then the mixture, NaNi 0.6 Mn 0.3 Fe 0.1 O2, acetylene black, and PVDF are dispersed in NMP solvent to form a positive electrode paste. Then, the positive electrode paste is uniformly coated on an aluminum foil current collector and punched into positive electrode sheets after vacuum drying at 120 °C.
[0070] The soft carbon negative electrode particles, acetylene black, and CMC are dispersed in NMP solvent at a mass ratio of 95:3.5:1.5 to form a negative electrode slurry. Then, the negative electrode slurry is uniformly coated on a copper foil current collector and punched into negative electrode sheets after vacuum drying at 60°C.
[0071] Using NaPF6 as the sodium salt, NaPF6 is dissolved in a mixed solvent of EC / DMC with a volume ratio of 4:6, and then 1 wt% fluoroethylene carbonate (FEC) is added as a film-forming additive to obtain an electrolyte. Among them, the concentration of the sodium salt in the electrolyte is 1.0 mol / L, and the conductivity of the electrolyte is ~12 mS / cm (25°C).
[0072] A PE ceramic membrane (PE separator loaded with 10 wt% BN) with a thickness of 13 μm is used.
[0073] A mechanical deformation-triggered CID is adopted, and the trigger threshold is set to 0.8 ± 0.05 MPa. The response time is verified to be <10 s through the spring stiffness coefficient.
[0074] Then, the above positive electrode sheet, negative electrode sheet, and separator are stacked into a 32700 cylindrical battery cell, and then the electrolyte is injected. The injection amount of the electrolyte is 3.5 g / Ah. After that, the CID device and the cap are installed, and after vacuum packaging, it is pre-charged (0.1C), aged (48 h), and formed (0.2C) to be activated to obtain a sodium-ion battery.
[0075] Example 5
[0076] Weigh NaNi 0.6 Mn 0.3 Fe 0.1 O2, Na2CO3 particles with a particle size of 1 μm, FeCl3, acetylene black, and PVDF according to a mass ratio of 92.7:2:0.3:3.5:1.5. First, the Na2CO3 particles and FeCl3 are premixed to form a mixture, and then the mixture, NaNi 0.6 Mn 0.3 Fe 0.1 O2, acetylene black, and PVDF are dispersed in NMP solvent to form a positive electrode slurry. Then, the positive electrode slurry is uniformly coated on an aluminum foil current collector and punched into positive electrode sheets after vacuum drying at 120°C.
[0077] The soft carbon negative electrode particles, acetylene black, and CMC are dispersed in NMP solvent at a mass ratio of 95:3.5:1.5 to form a negative electrode slurry. Then, the negative electrode slurry is uniformly coated on a copper foil current collector and punched into negative electrode sheets after vacuum drying at 60°C.
[0078] NaPF6 was used as the sodium salt. NaPF6 was dissolved in a mixed solvent of EC / DMC with a volume ratio of 4:6, and then 1 wt% of fluoroethylene carbonate (FEC) was added as a film-forming additive to obtain an electrolyte. Among them, the concentration of the sodium salt in the electrolyte was 1.0 mol / L, and the conductivity of the electrolyte was ~12 mS / cm (25 °C).
[0079] A PE ceramic membrane (a PE separator loaded with 10 wt% BN) with a thickness of 13 μm was used.
[0080] A mechanical deformation-triggered CID was adopted, and the trigger threshold was set to 0.6 ± 0.05 MPa. The response time was verified to be <10 s through the spring stiffness coefficient.
[0081] Then, the above positive electrode sheet, negative electrode sheet, and separator were stacked into a 32700 cylindrical battery cell, and then the electrolyte was injected. The injection amount of the electrolyte was 3.5 g / Ah. After that, the CID device and the cap were installed, and after vacuum packaging, it was pre-charged (0.1C), aged (48 h), and formed (0.2C) to be activated, obtaining a sodium-ion battery.
[0082] Example 6
[0083] Weigh NaNi 0.6 Mn 0.3 Fe 0.1 O2, Na2CO3 particles with a particle size of 1 μm, FeCl3, acetylene black, and PVDF according to a mass ratio of 91.4:3:0.6:3.5:1.5. First, the Na2CO3 particles and FeCl3 were premixed to form a mixture, and then the mixture, NaNi 0.6 Mn 0.3 Fe 0.1 O2, acetylene black, and PVDF were dispersed in an NMP solvent to form a positive electrode slurry. Then, the positive electrode slurry was evenly coated on an aluminum foil current collector and punched into a positive electrode sheet after vacuum drying at 120 °C.
[0084] The soft carbon negative electrode particles, acetylene black, and CMC were dispersed in an NMP solvent according to a mass ratio of 95:3.5:1.5 to form a negative electrode slurry. Then, the negative electrode slurry was evenly coated on a copper foil current collector and punched into a negative electrode sheet after vacuum drying at 60 °C.
[0085] NaPF6 was used as the sodium salt. NaPF6 was dissolved in a mixed solvent of EC / DMC with a volume ratio of 4:6, and then 1 wt% of fluoroethylene carbonate (FEC) was added as a film-forming additive to obtain an electrolyte. Among them, the concentration of the sodium salt in the electrolyte was 1.0 mol / L, and the conductivity of the electrolyte was ~12 mS / cm (25 °C).
[0086] Use a PE ceramic membrane (a PE separator loaded with 10 wt% BN), with a thickness of 13 μm.
[0087] Adopt a mechanically deformed triggered CID, set the trigger threshold to 0.8 ± 0.05 MPa, and verify that the response time is < 10 seconds through the spring stiffness coefficient.
[0088] Then stack the above positive electrode sheet, negative electrode sheet, and separator into a 32700 cylindrical battery cell, then inject the electrolyte, with the electrolyte injection amount being 3.5 g / Ah. After that, install the CID device and the cap, and after vacuum packaging, activate it through pre-charging (0.1C), aging (48 h), and formation (0.2C) to obtain a sodium-ion battery.
[0089] Comparative Example 1
[0090] The difference between Comparative Example 1 and Example 1 is only that NaNi 0.6 Mn 0.3 Fe 0.1 O2, acetylene black, and PVDF are dispersed in NMP solvent in a mass ratio of 95:3.5:1.5 to form a positive electrode slurry. Then, the positive electrode slurry is uniformly coated on an aluminum foil current collector, and after vacuum drying at 120 °C, it is punched into a positive electrode sheet.
[0091] Comparative Example 2
[0092] The difference between Comparative Example 2 and Example 1 is only that NaNi 0.6 Mn 0.3 Fe 0.1 O2, Na2CO3 particles with a particle size of 5 μm, acetylene black, and PVDF are dispersed in NMP solvent in a mass ratio of 94.5:0.5:3.5:1.5 to form a positive electrode slurry. Then, the positive electrode slurry is uniformly coated on an aluminum foil current collector, and after vacuum drying at 120 °C, it is punched into a positive electrode sheet.
[0093] Comparative Example 3
[0094] The difference between Comparative Example 3 and Example 1 is only that a mechanically deformed triggered CID is adopted, and the trigger threshold is set to 1.2 MPa.
[0095] Conduct overcharge tests on the sodium-ion batteries of Examples 1 - 6 and Comparative Examples 1 - 3, and the results are shown in Table 1.
[0096] Table 1 Overcharge test results of sodium-ion batteries
[0097]
[0098] As can be seen from Table 1, by optimizing the synergistic effect of the gas generation mechanism inside the battery cell and the CID trigger threshold, the present invention ensures that the internal temperature of the battery cell is always controlled below the thermal runaway critical point of 150°C during overcharging, thereby eliminating the risk of thermal runaway.
[0099] In addition, the gas components after overcharging test of the sodium-ion battery in Example 2 were analyzed, and the results were as follows: the volume fraction of carbon dioxide was 34.17%, the volume fraction of hydrogen was 24.49%, the volume fraction of carbon monoxide was 18.07%, the volume fraction of nitrogen was 10.93%, the volume fraction of methane was 3.69%, the volume fraction of ethane was 3.59%, the volume fraction of oxygen was 3.48%, the volume fraction of ethylene was 0.87%, and the volume fraction of propylene was 0.71%.
[0100] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as the scope described in this specification.
[0101] The above-described embodiments only represent several implementation manners of the present invention. The description is relatively specific and detailed, but it should not be construed as a limitation on the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent should be subject to the appended claims.
Claims
1. A sodium ion battery comprising a positive electrode sheet, a separator, a negative electrode sheet, an electrolyte, and a current interruption device, characterized in that: The sodium ion battery satisfies the following two conditions: (1) The positive electrode active material layer of the positive electrode sheet contains gas generating particles and a catalyst. Among them, the gas generating particles are selected from sodium carbonate and / or sodium oxalate, and the catalyst is selected from iron chloride and / or aluminum chloride. The mass fraction of the gas generating particles in the positive electrode active material layer is greater than the mass fraction of the catalyst in the positive electrode active material layer, and the sum of the mass fractions of the gas generating particles and the catalyst in the positive electrode active material layer is within 4%; (2) The triggering threshold of the current interruption device is 0.55 MPa - 0.85 MPa.
2. The sodium ion battery according to claim 1, characterized in that The mass ratio of the gas generating particles to the catalyst is 5:1 - 10:
1.
3. The sodium ion battery according to claim 1, characterized in that, The mass fraction of the gas generating particles in the positive electrode active material layer is above 0.5%, and the mass fraction of the catalyst in the positive electrode active material layer is below 0.8%.
4. The sodium ion battery according to claim 1, characterized in that, The mass fraction of the gas generating particles in the positive electrode active material layer is 0.5% - 3%.
5. The sodium ion battery according to claim 1, wherein The mass fraction of the catalyst in the positive electrode active material layer is 0.1% - 0.6%.
6. The sodium ion battery according to claim 1, characterized in that, The particle size of the gas generating particles is 0.1 μm - 10 μm.
7. The sodium ion battery according to any one of claims 1 to 6, characterized in that, The positive electrode active material layer at least includes a layered metal oxide positive electrode material.
8. The sodium-ion battery according to any one of claims 1 to 6, characterized in that, The triggering threshold of the current interruption device is 0.65 MPa - 0.75 MPa.
9. The sodium-ion battery according to any one of claims 1 to 6, characterized in that, The response time of the current interruption device is less than 10 seconds.
10. Application of a sodium ion battery according to any one of claims 1 to 9 in a battery module or a battery pack.
Citation Information
Patent Citations
Secondary battery
CN104471749A
Sealed nonaqueous electrolyte secondary battery and method of producing same
CN104508895A
Negative electrode of sodium ion battery and sodium ion battery
CN115275206A
Positive electrode with safe bottom layer and lithium ion battery
CN118782728A
Sodium ion battery and preparation method and application thereof
CN118919823A